Preparation method of porous carbon negative electrode material for sodium ion battery
By controlling the carbonization conditions and vapor deposition technology, the specific surface area and pore structure of porous carbon are adjusted, and the problems of low sodium storage capacity and ion transmission efficiency of negative electrode materials in sodium ion batteries are solved, and high energy density, initial Coulomb efficiency and rate performance are achieved. Improvement.
Patent Information
- Application Number
- CN202411567173.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The ion radius of Na+ in sodium ion batteries is large, making it difficult to configure electrode materials with high sodium storage capacity and fast ion transport, especially negative electrode materials.
Porous carbon is prepared by controlling the carbonization conditions, and carbon "steam" from a high volatile carbon source is deposited on the surface of the porous carbon by vapor phase, adjusting its specific surface area and pore structure, achieving the purpose of balancing the nanoporosity and specific surface area.
It significantly improves the reversible specific capacity, initial Coulomb efficiency and rate performance of porous carbon materials, and is suitable for sodium ion batteries.
Smart Images

Figure CN119409189A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries and relates to a method for preparing a porous carbon negative electrode material for a sodium ion battery. Background Art
[0002] With the massive use of fossil fuels and the increasing severity of global environmental problems, it is urgent to replace traditional energy with renewable energy. Advanced energy storage systems can overcome the temporal and geographical differences between the supply and demand of renewable energy. Compared with the successfully commercialized lithium-ion batteries, sodium-ion batteries have the advantages of low cost, abundant resources, and high safety, and are considered to be the current popular green energy storage devices. However, due to the + The ionic radius (102 pm) is larger than that of Li + (76 pm), which poses a significant challenge to configuring electrode materials, especially anode materials, with high sodium storage capacity and fast ion transport.
[0003] Carbon negative electrode materials have attracted much attention due to their high stability and relatively low cost. According to the "adsorption-filling" mechanism, the charge-discharge curve of carbon materials usually consists of a high-voltage slope region and a low-voltage platform region. Among them, the surface adsorption of open pore structures and defects can be Na + The storage of carbon provides active sites, thereby providing a slope capacity above 0.1V. The adsorption mechanism usually has faster diffusion kinetics and exhibits higher rate performance, but the carbon surface with a large specific surface area will undergo irreversible side reactions with the electrolyte, and the solid electrolyte film formed on the electrode surface will result in a low initial Coulombic efficiency. In addition, the platform capacity below 0.1V provided by nanopore filling contributes more to the energy density of the full battery, and this part of the capacity usually exhibits a higher initial Coulombic efficiency. Therefore, optimizing the pore structure of carbon materials and balancing the relationship between nanoporosity and specific surface area can make the material have both high energy density, initial Coulombic efficiency and excellent rate performance.
[0004] Based on this, the present invention aims to provide a porous carbon negative electrode material, which utilizes carbon "steam" produced by pyrolysis of a high-volatile carbon source, and utilizes a slow inert gas flow to bring the carbon "steam" around the porous carbon for vapor deposition, thereby achieving a balance between nanoporosity and specific surface area, thereby improving the initial coulombic efficiency and rate performance of the electrode material. Summary of the invention
[0005] In view of the above technical problems, the present invention aims to provide a method for preparing a porous carbon negative electrode material for a sodium ion battery, wherein porous carbons with different specific surface areas and pore volumes are prepared by controlling carbonization conditions, and then placed in the same tubular furnace for heating with a high-volatile carbon source, and the carbon "steam" pyrolyzed from the high-volatile carbon source is brought to the porous carbon by a slow inert gas flow for vapor deposition, which can effectively reduce the specific surface area of the porous carbon and make the obtained electrode material have a nanoporous structure suitable for sodium storage; the preparation method of the present invention is simple and easy to operate, has low energy consumption cost, and is highly controllable. It can be applied to sodium ion batteries to effectively improve the reversible specific capacity, initial coulombic efficiency and rate performance of the porous carbon material.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a porous carbon negative electrode material for a sodium ion battery is carried out in the following steps:
[0008] (1) KOH powder and a carbon-rich precursor with a particle size of 400-500 mesh are mixed evenly and placed in an activation kettle for carbonization for 1-4 hours under a nitrogen atmosphere. After cooling and taking out, they are soaked in 5M HCl, and repeatedly washed with deionized water and filtered to neutrality to remove residual metal K and its compounds. After drying at 110°C, porous carbon is obtained;
[0009] In the present invention, the specific surface area and pore development degree of porous carbon are controlled by controlling the carbonization conditions. If the pore development is insufficient, it will lead to fewer sodium storage active sites and lower capacity; if the pore volume or pore size is too large, the vapor deposition effect will not be obvious; therefore, the specific surface area should be controlled within 1000-2000m 2 / g, the pore size distribution should be concentrated below 5nm;
[0010] (2) placing the porous carbon prepared in step (1) and a high-volatile carbon source in the same tubular furnace, with the porous carbon placed in the center of the furnace and the high-volatile carbon source placed at the air inlet end, and depositing for 1 to 4 hours under a nitrogen atmosphere to obtain a porous carbon negative electrode material for a sodium ion battery.
[0011] As a limitation of the preparation method of the present invention, in step (1), the carbon-rich precursor is one or more biomass materials such as coal, asphalt, or coconut shell;
[0012] If asphalt or biomass is selected as the carbon-rich precursor, it needs to be pre-carbonized at 600°C for 1 hour.
[0013] As another limitation of the preparation method of the present invention, in step (1), the mass ratio of the KOH powder to the carbon-rich precursor is 1:(0.5-3).
[0014] As a third limitation of the preparation method of the present invention, in step (1), the carbonization temperature is 500-900° C., and the heating rate is 1-10° C. / min.
[0015] In the present invention, the carbonization conditions will affect the specific surface area of the porous carbon and the degree of pore development. If the carbonization temperature is greater than 900°C, violent K vapor will be generated, posing a safety hazard. If the carbonization temperature is less than 500°C, the pore-forming effect will not be obvious. The heating rate is controlled at 1 to 10°C / min, because if the heating rate is less than 1°C / min, energy consumption will increase, and if the heating rate is greater than 10°C / min, violent boiling will occur.
[0016] As a fourth limitation of the preparation method of the present invention, in step (2), the high volatile carbon source is one or more of low-rank coal, asphalt, resin or biomass.
[0017] As a fifth limitation of the preparation method of the present invention, in step (2), the mass ratio of the porous carbon to the high volatile carbon source is 1:(1-3).
[0018] In the present invention, the mass ratio of porous carbon to high volatile carbon source will affect the specific surface area and pore size of the porous carbon negative electrode material finally prepared. If the mass ratio is less than 1:1, it will result in a lower amount of deposited carbon and a larger specific surface area. If the mass ratio is greater than 1:3, it will result in an excessively high amount of deposited carbon, thereby reducing the sodium storage performance.
[0019] As a sixth limitation of the preparation method of the present invention, in step (2), the nitrogen gas flow rate is 5 to 20 mL / min.
[0020] As the seventh limitation of the preparation method of the present invention, in step (2), the deposition temperature is 500-1000° C., and the heating rate is 10-30° C. / min.
[0021] The deposition conditions of this step have a great influence on the reversible specific capacity, initial coulombic efficiency and rate performance of the finally prepared porous carbon negative electrode material. When the deposition temperature is greater than 1000°C, the order of the deposited carbon will be too high. When the deposition temperature is less than 500°C, the disorder of the deposited carbon will be too high, which will affect the sodium storage performance. The heating rate is controlled at 10-30°C / min. If the heating rate is less than 10°C / min, the volatile carbon will be lost during the heating process. If the heating rate is greater than 30°C / min, the volatile carbon will overflow too quickly, affecting the deposition effect.
[0022] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.
[0023] The above technical solution has the following advantages or beneficial effects:
[0024] 1. The porous carbon negative electrode material for sodium ion batteries prepared by the present invention can significantly improve the reversible capacity, initial coulombic efficiency and rate performance of the porous carbon.
[0025] 2. The present invention controls the thickness of the high volatile carbon source deposited on the porous carbon surface by controlling the amount of the high volatile carbon source, the distance between the high volatile carbon source and the porous carbon in the furnace, and the carbonization time.
[0026] 3. The pore structure control method of the porous carbon negative electrode material for sodium ion batteries prepared by the present invention has flexible process, low cost and is suitable for large-scale production.
[0027] The invention is suitable for preparing porous carbon negative electrode materials for sodium ion batteries.
[0028] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The SEM images of the porous carbon negative electrode materials for sodium ion batteries prepared in Example 1 and Comparative Example 1A of the present invention, wherein: a is the SEM image of Example 1, and b is the SEM image of Comparative Example 1A;
[0030] Figure 2 TEM images of the porous carbon negative electrode materials for sodium ion batteries prepared in Example 1 and Comparative Example 1A of the present invention, wherein a is the TEM image of Example 1, and b is the TEM image of Comparative Example 1A;
[0031] Figure 3 XRD diagrams of porous carbon negative electrode materials for sodium ion batteries prepared in Example 1 and Comparative Example 1A of the present invention;
[0032] Figure 4 The pore size distribution diagram of the porous carbon negative electrode material for sodium ion battery prepared in Example 1 and Comparative Example 1A group of the present invention is larger than 1 nm;
[0033] Figure 5 The pore size distribution diagram of the porous carbon negative electrode material for sodium ion battery prepared in Example 1 and Comparative Example 1A group of the present invention is less than 1 nm;
[0034] Figure 6 The first cycle charge and discharge curves of the porous carbon negative electrode material for sodium ion battery prepared in Example 1 and Comparative Example 1A of the present invention;
[0035] Figure 7 The reversible capacity diagram of the porous carbon negative electrode material for sodium ion battery prepared in Example 1 of the present invention and Comparative Example 1A group at different current densities. DETAILED DESCRIPTION
[0036] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0037] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0038] Example
[0039] Example 1
[0040] This embodiment prepares a porous carbon negative electrode material for a sodium ion battery, and the preparation process and steps are as follows:
[0041] (1) KOH powder and coal powder with a particle size of 400-500 mesh were mixed in a ratio of 1:1 and placed in an activation kettle. The mixture was heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere and kept warm for 1 hour. After cooling and taking out, the mixture was soaked in 5M HCl and repeatedly washed with deionized water to remove residual metal K and its compounds. The porous carbon was obtained after drying at 110°C.
[0042] (2) 1 g of the porous carbon obtained in step (1) is evenly spread in a corundum boat and placed in the center of a tubular furnace. A corundum boat containing 1 g of coal tar pitch is placed in the direction of the air inlet 20 cm away from the porous carbon. The temperature is increased to 800 ° C at a heating rate of 10 ° C / min in a nitrogen atmosphere (nitrogen gas flow rate is 20 mL / min) and kept warm for 4 h to obtain a porous carbon negative electrode material for sodium ion batteries.
[0043] Example 2
[0044] This embodiment prepares a porous carbon negative electrode material for a sodium ion battery, and the preparation process and steps are as follows:
[0045] (1) KOH powder and coal powder with a particle size of 400-500 mesh were mixed in a ratio of 1:0.5 and placed in an activation kettle. The mixture was heated to 900°C at a heating rate of 6°C / min in a nitrogen atmosphere and kept warm for 3 hours. After cooling and taking out, the mixture was soaked in 5M HCl and repeatedly washed with deionized water to remove residual metal K and its compounds. The mixture was dried at 110°C to obtain porous carbon.
[0046] (2) 1 g of the porous carbon prepared in step (1) is evenly spread in a corundum boat and placed in the center of a tubular furnace. A corundum boat containing 2 g of phenolic resin is placed in the direction of the air inlet 20 cm away from the porous carbon. The temperature is increased to 1000° C. at a heating rate of 20° C. / min under a nitrogen atmosphere (nitrogen gas flow rate of 10 mL / min) and kept warm for 3 h to obtain a porous carbon negative electrode material for a sodium ion battery.
[0047] Example 3
[0048] This embodiment prepares a porous carbon negative electrode material for a sodium ion battery, and the preparation process and steps are as follows:
[0049] (1) KOH powder and coal powder with a particle size of 400-500 mesh were mixed in a ratio of 1:3 and placed in an activation kettle. The mixture was heated to 500°C at a heating rate of 1°C / min under a nitrogen atmosphere and kept warm for 4 hours. After cooling and taking out, the mixture was soaked in 5M HCl and repeatedly washed with deionized water to remove residual metal K and its compounds. The porous carbon was obtained after drying at 110°C.
[0050] (2) 1 g of the porous carbon obtained in step (1) was evenly spread in a corundum boat and placed in the center of a tubular furnace. A corundum boat containing 3 g of coal tar pitch was placed in the direction of the air inlet 20 cm away from the porous carbon. The temperature was increased to 500 ° C at a rate of 30 ° C / min under a nitrogen atmosphere (nitrogen gas flow rate of 5 mL / min) and kept warm for 1 h to obtain a porous carbon negative electrode material for sodium ion batteries.
[0051] Example 4
[0052] This embodiment prepares a porous carbon negative electrode material for a sodium ion battery, and the preparation process and steps are as follows:
[0053] (1) The washed coconut shell was placed in a tube furnace for pre-carbonization at 600°C for 1 h, and then KOH powder and coconut shell with a particle size of 400-500 mesh were mixed in a ratio of 1:0.5 and placed in an activation kettle. The mixture was heated to 900°C at a heating rate of 6°C / min under a nitrogen atmosphere and kept warm for 4 h. After cooling and taking out, the mixture was soaked in 5M HCl and repeatedly washed with deionized water to remove residual metal K and its compounds. After drying at 110°C, porous carbon was obtained.
[0054] (2) 1 g of the porous carbon obtained in step (1) is evenly spread in a corundum boat and placed in the center of a tubular furnace. A corundum boat containing 1 g of coal tar pitch is placed in the direction of the air inlet 20 cm away from the porous carbon. The temperature is increased to 800 ° C at a heating rate of 10 ° C / min in a nitrogen atmosphere (nitrogen gas flow rate is 20 mL / min) and kept warm for 4 h to obtain a porous carbon negative electrode material for sodium ion batteries.
[0055] Comparative Example
[0056] In order to explore the influence of different parameters in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were carried out. Different porous carbon negative electrode materials for sodium ion batteries were prepared in the following comparative examples, as follows:
[0057] Comparative Example 1
[0058] Group A: This group of comparative examples prepares a porous carbon negative electrode material similar to that of Example 1, except that step (2) is not performed, i.e., the porous carbon prepared by step (1) is directly used as the negative electrode material of the sodium ion battery.
[0059] Group B: This group of comparative examples prepares a porous carbon negative electrode material similar to that of Example 2, except that step (2) is not performed, i.e., the porous carbon prepared by step (1) is directly used as the negative electrode material of the sodium ion battery.
[0060] Group C: This group of comparative examples prepares a porous carbon negative electrode material similar to that of Example 3, except that step (2) is not performed, i.e., the porous carbon prepared by step (1) is directly used as the negative electrode material of the sodium ion battery.
[0061] Group D: This group of comparative examples prepares a porous carbon negative electrode material similar to that of Example 4, except that step (2) is not performed, i.e., the porous carbon prepared by step (1) is directly used as the negative electrode material of the sodium ion battery.
[0062] Comparative Example 2
[0063] The present comparative example prepares a porous carbon negative electrode material similar to that of Example 1, except that in step (1), the carbonization process is heated to 450° C. at a heating rate of 0.5° C. / min and maintained at that temperature for 4 h.
[0064] Comparative Example 3
[0065] The present comparative example prepares a porous carbon negative electrode material similar to that of Example 1, except that in step (2), the ratio of coal tar pitch to porous carbon is 1:5, and the other parameters are the same as those of Example 1.
[0066] Comparative Example 4
[0067] In this comparative example, a porous carbon negative electrode material similar to that in Example 1 is prepared, with the only difference being that in step (2), the nitrogen gas flow rate is 30 mL / min, and the other parameters are the same as those in Example 1.
[0068] Comparative Example 5
[0069] In this comparative example, a porous carbon negative electrode material similar to that in Example 1 is prepared, except that in step (2), the carbon deposition process is heated to 400° C. at a heating rate of 12° C. / min and kept at this temperature for 4 h.
[0070] Performance Testing
[0071] (I) The specific surface area and total pore volume of the porous carbon negative electrode materials prepared in Examples 1 to 4 and Comparative Examples 1A to 1D were tested, and the specific data are shown in the following table:
[0072]
[0073] As can be seen from the above table, the specific surface area and total pore volume of Examples 1 to 4 are greatly reduced compared with Groups A to D of Comparative Example 1, indicating that the deposited carbon is effectively attached to the porous carbon surface.
[0074] (II) The morphology, structure and related performance tests of the porous carbon negative electrode materials prepared in Example 1 and Comparative Example 1A were performed as follows:
[0075] Figure 1 1 and 1A are SEM images of Example 1 and Comparative Example 1, wherein: a is the SEM image of Example 1, and b is the SEM image of Comparative Example 1A. It can be seen from the figures that the surface of the porous carbon becomes smooth after vapor deposition, which is due to the fact that the pores of the porous carbon are filled with deposited carbon.
[0076] Figure 2 TEM images of Example 1 and Comparative Example 1A, wherein: a is the TEM image of Example 1, and b is the TEM image of Comparative Example 1A. It can be seen from the figures that an obvious and uniform deposited carbon layer appears on the surface of the porous carbon, and the internal carbon microcrystalline structure does not undergo obvious changes.
[0077] Figure 3 The XRD graphs of Example 1 and Comparative Example 1A group show that the porous carbon negative electrode materials prepared in Example 1 and Comparative Example 1A group both show obvious low diffraction angle upturn, indicating that the carbon interior still maintains a high porosity after vapor deposition. The peak intensity of the porous carbon negative electrode material in Example 1 is increased compared to that in Comparative Example 1A group, indicating that vapor deposition can effectively improve the order of porous carbon.
[0078] Figure 4 This is a distribution diagram of pore sizes greater than 1 nm for the porous carbon negative electrode materials prepared in Example 1 and Comparative Example 1A. It can be seen from the diagram that the pore sizes of the porous carbon negative electrode materials prepared in Example 1 and Comparative Example 1A are all concentrated below 3 nm. Compared with the porous carbon negative electrode material in Comparative Example 1A, the pores with pore sizes above 1 nm in Example 1 are greatly reduced.
[0079] Figure 5 This is a pore size distribution diagram of the porous carbon negative electrode materials prepared in Example 1 and Comparative Example 1A group with a pore size less than 1 nm. It can be seen from the figure that compared with the porous carbon negative electrode material in Example 1 group A, the pores with a pore size below 1 nm are greatly reduced, and only pores with a pore size of about 0.6 nm exist.
[0080] Figure 6 The first cycle charge and discharge curves of Example 1 and Comparative Example 1A group are shown. It can be seen from the figure that compared with the porous carbon negative electrode material of Comparative Example 1A group, the charge and discharge curves of Example 1 show obvious platform areas, and the first charge capacity and initial coulomb efficiency are greatly improved.
[0081] Figure 7 The reversible capacity diagram of the electrode materials prepared in Example 1 and Comparative Example 1A group at different current densities. It can be seen from the figure that compared with the porous carbon negative electrode material in Comparative Example 1A group, Example 1 maintains better capacity at high current, that is, the rate performance is greatly improved.
[0082] (III) The porous carbon negative electrode material prepared in Examples 1 to 4 and Comparative Examples 1 to 5 was used as the negative electrode active material of the sodium ion battery, polyvinylidene fluoride (PVDF) was used as a binder, and Super P was used as a conductive agent. The three were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 18:1:1, coated on a copper foil, and cut into electrode sheets after drying. 1 mol / L NaPF6 (EC:DEC=1:1) was used as an electrolyte, and metallic sodium was used as a counter electrode to assemble a sodium ion half-cell for relevant electrochemical performance tests. The test data are shown in the following table:
[0083]
[0084] It can be seen from the above table that the first cycle charging capacity and initial coulombic efficiency of the porous carbon negative electrode materials prepared in Examples 1 to 4 are greatly improved compared with those prepared in Comparative Examples 1 to 5.
[0085] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a porous carbon negative electrode material for a sodium ion battery, characterized in that: Follow these steps in order: (1) KOH powder and a carbon-rich precursor with a particle size of 400-500 mesh are mixed evenly and placed in an activation kettle for carbonization for 1-4 hours under a nitrogen atmosphere. After cooling and taking out, they are soaked in 5M HCl, and repeatedly washed with deionized water and filtered until neutral to remove residual metal K and its compounds. After drying at 110°C, porous carbon is obtained; (2) placing the porous carbon prepared in step (1) and a high-volatile carbon source in the same tubular furnace, with the porous carbon placed in the center of the furnace and the high-volatile carbon source placed at the air inlet end, and depositing for 1 to 4 hours under a nitrogen atmosphere to obtain a porous carbon negative electrode material for a sodium ion battery.
2. The method for preparing a porous carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (1), the carbon-rich precursor is one or more biomass materials such as coal, asphalt, or coconut shell; If asphalt or biomass is selected as the carbon-rich precursor, it needs to be pre-carbonized at 600°C for 1 hour.
3. The method for preparing a porous carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (1), the mass ratio of the KOH powder to the carbon-rich precursor is 1: (0.5~3)。 4. The method for preparing a porous carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (1), the carbonization temperature is 500-900°C, and the heating rate is 1-10°C / min.
5. The method for preparing a porous carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (2), the high volatile carbon source is one or more of low-rank coal, asphalt, resin or biomass.
6. The method for preparing a porous carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (2), the mass ratio of the porous carbon to the high volatile carbon source is 1:(1-3).
7. The method for preparing a porous carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (2), the nitrogen gas flow rate is 5 to 20 mL / min.
8. The method for preparing a porous carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (2), the deposition temperature is 500-1000° C., and the heating rate is 10-30° C. / min.
Citation Information
Patent Citations
Tobacco stalk based porous carbon material for electrodes of super capacitor and preparation method thereof
CN102311113A
Hard carbon material and preparation method and application thereof
CN115744874A
Environment-friendly high-cycling-stability biomass hard carbon negative electrode material for sodium-ion battery and preparation method of green environment-friendly high-cycling-stability biomass hard carbon negative electrode material
CN117509609A
Biomass hard carbon material as well as preparation method and application thereof
CN118062823A
Method for preparing hard carbon negative electrode material rich in closed pores from porous carbon and application of hard carbon negative electrode material
CN118239487A